Pelletized Organomineral vs. Inorganic Nitrogen and Phosphorus Fertilizers: Impact on Wheat Nutritional Status, Productivity, and Grain Quality - Carciochi, Walter Daniel (2024)
The literature presents conflicting findings regarding the efficacy of organomineral fertilizers (OMFs) in comparison to inorganic counterparts. Furthermore, limited information is available comparing these fertilizer sources in terms of wheat (Triticum aestivum L.) productivity, especially in Mollisols from humid regions. Therefore, this study aims to evaluate and compare the effectiveness of OMFs with that of inorganic fertilizers as nitrogen (N) and phosphorus (P) sources, with a focus on their influence on wheat nutrition, yield, and grain quality. Three field trials were conducted in the Argentinean Pampas to compare OMFs enriched with N and P (OMF + N and OMF + P) against urea and monoammonium phosphate, respectively. The greenness index (GI) and normalized difference vegetation index (NDVI) were measured to characterize the nutritional status of the crop. Grain yield and quality parameters (i.e., hectolitre weight, protein, and gluten concentration) were determined. The main findings of this study were: (i) the combined application of OMF + N and OMF + P increased wheat yield by 13% (588 kg ha− 1) compared to inorganic fertilizers; (ii) OMF + N exhibited slower N release compared to urea; (iii) GI and, particularly, NDVI were related to grain yield (R2 = 0.71 and 0.81, respectively); and (iv) fertilizer sources did not affect grain quality parameters. In conclusion, OMFs offer a suitable option for contributing to the recycling of nutrients in agroecosystems and reducing reliance on inorganic fertilizers, allowing increased wheat yield while maintaining grain quality in Mollisols of humid regions.